Cytotoxicity of NeoMTA Plus, ProRoot MTA and Biodentine on human dental pulp stem cells - AKKOÇ, TUNÇ (ELSEVIER TAIWAN, 2021)
Background/purpose: Dental pulp stem cells (DPSCs) play a crucial role in the tis-sue healing process through odontoblast like cell differentiation. The aim of this study was to evaluate the biocompatibility and compare the potential invitro cytotoxic effects of NeoMTA Plus, ProRootMTA and Biodentine on human dental pulp stem cells (hDPSCs). Materials and methods: To assess the effects of NeoMTA Plus, ProRoot MTA and Biodentine ex-tracts at 1st, 3rd and 7th d on hDPCs, cell populations was determined by flow cytometry using an Annexin V detection kit. The data were analyzed statistically using the Kruskal-Wallis test. A p < 0.05 was considered as statistically significant. Results: All groups showed cell viability similar to that of the control group on 1st, 3rd and 7th d. Although Biodentine exhibited higher cell viability rates than the other material groups, no statistically significant differences were noted between the sampled days (p > 0.05). Conclusion: All materials extracts are not cytotoxic and do not induce apoptosis in the hDPSCs. These results suggest that all the tested materials can lead to positive outcomes when used as reparative biomaterials. (c) 2020 Association for Dental Sciences of the Republic of China. Publishing services by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons. org/licenses/by-nc-nd/4.0/).
Keywords: Cytotoxicity; Dental pulp stem cells; Mineral trioxide aggregate; MINERAL TRIOXIDE AGGREGATE; ODONTOBLASTIC DIFFERENTIATION; TRICALCIUM SILICATE; COLOR STABILITY; IN-VITRO; PROLIFERATION; BIOAGGREGATE; EXPRESSION; MIGRATION; TEETH